2017
DOI: 10.2217/imt-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Immunotherapy Modulates Sensitivity of Treg Cells to Apoptosis in a Rat Model of Allergic Asthma

Abstract: Apoptosis of Treg cells is increased following allergen sensitization-challenge via extrinsic, intrinsic and perforin/granzyme pathways and allergen immunotherapy decreased the sensitivity to apoptosis of Treg cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Critically, SATB1 but not FOXP3 expression in Tregs correlated with the alleviation of clinical symptoms [125••]. Reduced sensitivity to apoptosis in FOXP3 + Tregs is another proposed AIT-induced mechanism of propelling tolerance, as seen in a murine asthma model [106].…”
Section: Effect Of Ait On Regulatory T Cellsmentioning
confidence: 99%
“…Critically, SATB1 but not FOXP3 expression in Tregs correlated with the alleviation of clinical symptoms [125••]. Reduced sensitivity to apoptosis in FOXP3 + Tregs is another proposed AIT-induced mechanism of propelling tolerance, as seen in a murine asthma model [106].…”
Section: Effect Of Ait On Regulatory T Cellsmentioning
confidence: 99%
“…The traditional Th1/Th2 imbalance theory cannot explain all the pathogenesis. Presently, a number of studies have focused on Treg cells to investigate the pathognesis ( 36 , 37 ). Our findings demonstrated that AOS treatment reduced the serum levels of Th1 and Th2 cytokines (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs induced basophil activation through the release of IL-3. It has been suggested that Tregs might also promote tumor evasion by activating basophils to augment and sustain Th2 responses in TME by secreting IL-3 ( 215 ).…”
Section: Basophils and Pancreatic Cancermentioning
confidence: 99%